Prevalence and Socio-Demographic Correlates (Age and Parity) of HBV Infection Among Pregnant Women in Oyo State - Aina; M. A. (African Journal of Health Nursing and Midwifery, 2026)
Hepatitis B virus (HBV) is still a major public health problem in sub-Saharan Africa, especially because of the risk of transmission of the infection from mothers to their babies at birth. This study set out to establish the level of sero-prevalence of HBV, maternal perception and THE relationship between maternal age, parity, and sero-status in Oyo State. A Descriptive cross-sectional design was used and consisted of 100 respondents for the questionnaire and 622 respondents for the laboratory. The HBV sero-prevalence came out to be 6.8%. There was a general lack of understanding of long-term effects and general epidemiological trends, although the respondents generally had an understanding of the transmission routes. There were significant correlations of HBV status with maternal age (p=0.002) and parity (p=0.019), with the highest prevalence being seen in women aged 35–44 and with five pregnancies. The investigation concludes that HBV is a persistent problem that needs to be addressed by enhancing routine antenatal screening, health education targeting mothers and strengthening vaccination programs to stop mother-to-child transmission.